(untitled) (Revista educación, investigación, innovación y transferencia, 2025)
Organic Law 3/2020, of December 29, which modifies Organic Law 2/2006, of May 3, on Education (LOMLOE), recognizes the importance of addressing sustainable development in accordance with the provisions of the Agenda 2030. Thus, Education for Sustainable Development and global citizenship must be incorporated into the educational plans, projects and programs of all non-university education, including the knowledge, skills, values and attitudes that all people need to live a fruitful life, making informed decisions and taking an active role in facing and solving the problems common to global citizens. The general objective of this research is to analyze those practical, attitudinal and behavioral aspects that teachers use in their classrooms related to sustainable development. To do this, a questionnaire is designed to collect information related to the treatment of transversal content in class, such as equality, the environment, peace education, group work in the elaboration of pacts and alliances, etc., combining closed and open questions that offer the opportunity to develop and learn about educational practices in the work of these values. Likewise, a correlation is made of the information obtained based on the stage in which teaching is taught and the years of teaching experience. The collection of information from the applied questionnaire has made it possible to know and determine a good score in relation to the attitudes and behaviors of the teachers, which translates into the good predisposition of the teachers towards the work of sustainable development in their classrooms.